Pengaruh Penggunaan Bahan Pengawet Alami pada Ikan Layang Segar (Decapterus russelli) pada Umur Simpan Tiga Hari Terhadap Mutu - Jefrianto Nggau Behar; I Gde Suranaya Pandit; Ni Made Darmadi (Fakultas Pertanian, Universitas Warmadewa, 2021)
This study is aimed at recognizing the effect that the use of natural preservative material might have on the fresh gliding fish (decapcontinue russelli) at the age of three days to quality. Research carried out in july 2020 at the waregod university agricultural departement and the marine service laboratory and the uptd fishheries the quality testing and application of fisheries results. the design used is a complete randomness (RAL) with a single factor in treatment of different natural preservative material, with four different treatment and four deuteronomy without preservative material, grinding ice 4:1, salt 4:1 and lime 10% concentration. objective observations include a total volatile base, water level, ph, total acid, salinity and microbial test, the total plate count. best research result are derived on the use of the pulverized ice 4:1 ingredient from objective observation (a total volatile base 22,27 mg, water level 78,23%, pH 6,95, total acid 0,39%, salt level 5,03%, total plate count 7,7x103c/g ). while from a subjective observationt of your best judgment is on treatment with materials salt presrvative 4:1 (mark 7,13, smell 6,68 and texture 7,30).